2014
DOI: 10.1016/j.virol.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

KSHV LANA and EBV LMP1 induce the expression of UCH-L1 following viral transformation

Abstract: Ubiquitin C-terminal Hydrolase L1 (UCH-L1) has oncogenic properties and is highly expressed during malignancies. We recently documented that Epstein-Barr virus (EBV) infection induces uch-l1 expression. Here we show that Kaposi's Sarcoma-associated herpesvirus (KSHV) infection induced UCH-L1 expression, via cooperation of KSHV Latency-Associated Nuclear Antigen (LANA) and RBP-Jκ and activation of the uch-l1 promoter. UCH-L1 expression was also increased in Primary Effusion Lymphoma (PEL) cells co-infected with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
(110 reference statements)
1
10
0
Order By: Relevance
“…We previously reported that UCH-L1 expression is upregulated during EBV-mediated transformation of B-lymphocytes ( 52 ) and by expression of LMP1 in epithelial cells ( 50 ). However, whether LMP1 is directly associated with UCH-L1 was still unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that UCH-L1 expression is upregulated during EBV-mediated transformation of B-lymphocytes ( 52 ) and by expression of LMP1 in epithelial cells ( 50 ). However, whether LMP1 is directly associated with UCH-L1 was still unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of UCH-L1 in an adult organism is restricted to the central nervous and reproductive systems, but its de novo expression has been reported in numerous cancers such as lung cancer ( 45 , 46 ), colorectal cancer ( 47 ), bladder cancer ( 48 ), and breast cancer ( 49 ). Tumor viruses such as EBV, human papillomavirus (HPV), and Kaposi’s sarcoma-associated herpesvirus (KSHV) also induce UCH-L1 expression during cell transformation ( 50 54 ). A substantial amount of published data has demonstrated that UCH-L1 acts as a pro-oncogenic and prometastatic molecule in cell culture and in animal model systems ( 46 , 51 , 55 60 ).…”
Section: Introductionmentioning
confidence: 99%
“… 116 In general, LMP1 activation leads to overexpression of antiapoptotic molecules, such as B-cell CLL/lymphoma 2 (Bcl-2), 117 myeloid cell leukemia 1 (Mcl-1) 118 and BCL-2-related protein A1 (Bcl2A1/Bfl-1), 116 , 119 and blocks p53-mediated apoptosis through the induction of anti-apoptotic protein A20, 120 unfolded protein response (UPR)-induced apoptosis in B cells 116 and ubiquitin C-terminal hydrolase L1 (UCH-L1) with oncogenic properties. 121 Complementary to its proliferative function, LMP1 inhibits proapoptotic factors such as Bax 122 and induces autocrine factors, such as chemokine (C–C motif) ligand 3 (CCL3) and chemokine (C–C motif) ligand 4 (CCL4), to promote cell proliferation. 123 LMP1 also enhances cancer cell motility by upregulating TNF α-induced protein 2 (TNFAIP2) through NF-κB activation.…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…Using previously described siRNA constructs and methods, Raji cells were transiently transfected to knockdown LMP1, with a two-base mutation siRNA used as a control 61 .…”
Section: Methodsmentioning
confidence: 99%